Perancangan Infrastruktur Virtual Laboratory Multi-Layanan Berbasis Cloud Computing Menggunakan Metode NDLC - Metalika Gunena; Anritsu Steven Christian Polii; Antonius P. G. Manginsela; Franky Manoppo; Olga Engelien Melo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The limited hardware specifications of student devices remain a major obstacle in conducting computation-based practical courses in higher education, particularly in practicums that require applications with high computational resource demands, such as programming software, network simulation tools, and various other supporting applications, which often cannot run optimally on student devices with low specifications. This condition causes practical learning to become inconsistent and highly dependent on the capability of each student's personal device. Based on this problem, this research aims to design and simulate a cloud computing-based Virtual Laboratory system that can be accessed through a web browser without requiring high hardware specifications on the user side, while also contributing an integrated virtual laboratory architecture that combines three cloud computing service models simultaneously, namely Infrastructure as a Service (IaaS), Platform as a Service (PaaS), and Software as a Service (SaaS). As a solution, IaaS is built using Proxmox Virtual Environment (VE) as a type-1 hypervisor, pfSense as a virtual firewall, Ubuntu Server as the service host, and Docker as the containerization platform, along with Cloudflare Tunnel using a Zero Trust architecture to ensure accessibility from outside the campus network without dependence on a static public IP. The system is equipped with multi-role authentication (student, lecturer, admin) based on Student ID Number (NIM) or National Lecturer ID Number (NIDN) verification and OTP verification, a QR code-based Attendance module integrated with the Timetable module, and a main portal built as an installable Progressive Web App (PWA) on user devices. The system was developed using the Network Development Life Cycle (NDLC) method. Preliminary functional testing results show that all services in the Programming Class and Network Class, including the Attendance and Timetable modules, were successfully accessed from outside the campus network, and the multi-role authentication system functioned as designed.